Magnetic paste

By adding acid dispersant to the magnetic paste, the viscosity is reduced and the mechanical strength and bonding strength is improved, the problem of the increase in viscosity of the magnetic paste when it contains magnetic powder is solved, and the high-density circuit substrate and inductor components are realized. Manufacturing demand.

CN112424889BActive Publication Date: 2024-12-24AJINOMOTO CO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980048580.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2019-07-24
Publication Date
2024-12-24
Estimated Expiration
2039-07-24

AI Technical Summary

Technical Problem

When the existing magnetic paste contains magnetic powder, the viscosity increases lead to poor printing properties and the mechanical strength and adhesion strength also become worse, especially when the large amount of magnetic powder is filled, the performance is more obvious.

Method used

By using magnetic paste containing acid dispersant, the viscosity is reduced, and the mechanical strength and adhesion strength are improved. Specific ingredients include magnetic powders, epoxy resins, acid dispersants and curing agents. The pH value of the acid dispersant is lower than 4. And its content is between 0.1% and 5%.

Benefits of technology

Magnetic paste with low viscosity, excellent mechanical strength and adhesive strength is achieved, and is suitable for the manufacturing of high-density circuit substrates and inductor components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112424889B_ABST
    Figure CN112424889B_ABST
Patent Text Reader

Abstract

The present invention provides a magnetic paste having low viscosity and capable of obtaining a cured product having excellent mechanical strength and adhesion strength, and a cured product, a circuit board, and an inductor component using the magnetic paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a magnetic paste and a cured product, a circuit board and an inductor component using the magnetic paste. Background Art

[0002] With the recent demand for miniaturization and thinning of electronic devices, circuit boards used in electronic devices are also required to be miniaturized and have high wiring density. As such a circuit board, a board formed by filling a through hole with a paste material is known.

[0003] For example, Patent Document 1 describes a filling resin containing magnetic particles such as iron (III) oxide and cobalt iron oxide as a resin for filling through holes in a circuit board for an inductor component.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: Japanese Patent Application Publication No. 2016-197624. Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] In order to improve the relative magnetic permeability of the solidified product of the magnetic paste such as the filled resin of Patent Document 1, a method of making the filled resin contain magnetic powder can be considered. However, if the magnetic paste contains magnetic powder, the viscosity of the magnetic paste increases, and the printability of the magnetic paste may deteriorate. In addition, if the magnetic paste contains magnetic powder, the mechanical strength of the solidified product of the magnetic paste and the adhesion strength with the coating may deteriorate. In particular, when a paste containing a large amount of magnetic powder is used as the filled resin described in Patent Document 1, the viscosity, mechanical strength and adhesion strength become worse.

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a magnetic paste having low viscosity and capable of obtaining a cured product having excellent mechanical strength and adhesion strength even when containing magnetic powder, and a cured product, a circuit board, and an inductor component using the magnetic paste.

[0010] Technical solutions adopted to solve technical problems

[0011] The present inventors have conducted intensive studies to achieve the above object and have found that a cured product having low viscosity and excellent mechanical strength and adhesion strength can be obtained by using a magnetic paste containing an acidic dispersant, thereby completing the present invention.

[0012] That is, the present invention includes the following contents;

[0013] [1] A magnetic paste comprising:

[0014] (A) Magnetic powder,

[0015] (B) Epoxy resin,

[0016] (C) an acidic dispersant, and

[0017] (D) a curing agent;

[0018] [2] The magnetic paste according to [1], wherein the pH of the component (C) is lower than 4;

[0019] [3] The magnetic paste according to [1] or [2], wherein the pH of component (C) is 2 or more;

[0020] [4] The magnetic paste according to any one of [1] to [3], wherein the content of the component (C) is 0.1% by mass or more and 5% by mass or less, when the non-volatile component in the magnetic paste is 100% by mass;

[0021] [5] The magnetic paste according to any one of [1] to [4], wherein the component (D) contains an imidazole epoxy resin curing agent;

[0022] [6] The magnetic paste according to any one of [1] to [5], wherein the component (A) is at least one selected from iron oxide powder and iron alloy metal powder;

[0023] [7] The magnetic paste according to any one of [1] to [6], wherein the component (A) contains iron oxide powder.

[0024] The iron oxide powder comprises: ferrite containing at least one element selected from Ni, Cu, Mn and Zn;

[0025] [8] The magnetic paste according to any one of [1] to [7], wherein the component (A) comprises: an iron alloy metal powder containing at least one element selected from Si, Cr, Al, Ni and Co;

[0026] [9] The magnetic paste according to any one of [1] to [8], wherein the content of the component (A) is 70% by mass or more and 98% by mass or less, when the non-volatile component in the magnetic paste is 100% by mass;

[0027]

[10] The magnetic paste according to any one of [1] to [9], which is used to fill a through hole;

[0028]

[11] A cured product, which is the cured product of the magnetic paste according to any one of [1] to

[10] ;

[0029]

[12] A circuit board comprising:

[0030] A substrate having a through hole, and

[0031] A cured product of the magnetic paste according to any one of [1] to

[10] filled in the through-hole;

[0032]

[13] An inductor component comprising the circuit substrate described in

[12] .

[0033] Effects of the Invention

[0034] According to the present invention, it is possible to provide a magnetic paste having low viscosity and capable of obtaining a cured product having excellent mechanical strength and adhesion strength, and a cured product, a circuit board, and an inductor component using the magnetic paste.

[0035] Brief description of the attached figure

[0036] Figure 1 is a schematic cross-sectional view of a core substrate as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0037] Figure 2 is a schematic cross-sectional view of a core substrate in which a through hole is formed as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0038] Figure 3 is a schematic cross-sectional view showing a core substrate having a plated layer formed in a through hole as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0039] Figure 4 is a schematic cross-sectional view showing a core substrate in which a through hole is filled with a magnetic paste as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0040] Figure 5 is a schematic cross-sectional view showing the state of a core substrate after thermally curing a filled magnetic paste as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0041] Figure 6 is a schematic cross-sectional view showing a state of a core substrate after a solidified material is polished as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0042] Figure 7 is a schematic cross-sectional view showing a core substrate having a conductor layer formed on a polished surface as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0043] Figure 8is a schematic cross-sectional view showing a core substrate on which a pattern conductor layer is formed as an example of a method for manufacturing a circuit substrate according to the first embodiment;

[0044] Fig. 9 is a schematic cross-sectional view for explaining step (A) included in an example of a method for manufacturing a circuit board according to the second embodiment;

[0045] Fig.10 is a schematic cross-sectional view for explaining step (A) included in an example of a method for manufacturing a circuit board according to the second embodiment;

[0046] Fig.11 is a schematic cross-sectional view for explaining step (B) included in an example of the method for manufacturing a circuit board according to the second embodiment;

[0047] Fig.12 is a schematic cross-sectional view for explaining step (D) included in an example of the method for manufacturing a circuit board according to the second embodiment;

[0048] Fig.13 is a schematic plan view of an inductor component as an example, viewed from one side in the thickness direction thereof, the inductor component including a circuit substrate obtained by the method for manufacturing a circuit substrate according to the second embodiment;

[0049] Fig.14 1 is a schematic diagram showing a cut end face of an inductor component cut at a position indicated by a II-II dashed line as an example, the inductor component including a circuit substrate obtained by the method for manufacturing a circuit substrate according to the second embodiment;

[0050] Fig.15 It is a schematic plan view for explaining the structure of a first conductor layer in an inductor component as an example, the inductor component including a circuit board obtained by the method for manufacturing a circuit board according to the second embodiment. DETAILED DESCRIPTION

[0051] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings. It should be noted that each of the accompanying drawings is only to briefly illustrate the shape, size and configuration of the constituent elements to the extent that the invention can be understood. The present invention is not limited to the following description, and each constituent element may be appropriately changed. In the accompanying drawings used for the following description, the same constituent elements are marked with the same symbols, and repeated descriptions are sometimes omitted. In addition, the configuration described in the embodiments of the present invention is not limited to the configuration manufacturing or use of the illustrated examples.

[0052] [Magnetic paste]

[0053] The magnetic paste of the present invention comprises (A) magnetic powder, (B) epoxy resin, (C) acidic dispersant and (D) curing agent.

[0054] In the present invention, by containing (C) an acidic dispersant, the viscosity of the magnetic paste is reduced, and the printability becomes excellent. In addition, the mechanical strength and adhesion strength of the cured product can also be improved. In addition, the pot life of the viscosity of the magnetic paste is usually increased, and the obtained cured product can usually achieve an increase in relative permeability and a decrease in magnetic loss within a frequency range of 10 to 200 MHz.

[0055] The magnetic paste may further contain (E) other additives as necessary. Hereinafter, each component contained in the magnetic paste of the present invention will be described in detail.

[0056] <(A) Magnetic powder>

[0057] The magnetic paste contains (A) magnetic powder as (A) component. Examples of (A) magnetic powder include pure iron powder, Mg-Zn ferrite, Fe-Mn ferrite, Mn-Zn ferrite, Mn-Mg ferrite, Cu-Zn ferrite, Mg-Mn-Sr ferrite, Ni-Zn ferrite, Ba-Zn ferrite, Ba-Mg ferrite, Ba-Ni ferrite, Ba-Co ferrite, Ba-Ni-Co ferrite, Y ferrite, iron oxide powder (III), iron oxide such as ferroferric oxide, etc. Powder; iron alloy metal powders such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, or Fe-Ni-Co alloy powder; amorphous alloys such as Co-based amorphous alloys.

[0058] Among them, as (A) magnetic powder, it is preferred to include at least one selected from iron oxide powder and iron alloy metal powder. As iron oxide powder, it is preferred to include: ferrite containing at least one element selected from Ni, Cu, Mn and Zn. In addition, as iron alloy metal powder, it is preferred to include: iron alloy metal powder containing at least one element selected from Si, Cr, Al, Ni and Co.

[0059] As (A) magnetic powder, commercially available magnetic powder can be used. Specific examples of commercially available magnetic powder that can be used include: "M05S" manufactured by Powdertech Co., Ltd.; "PST-S" manufactured by Sanyo Special Steel Co., Ltd.; "AW2-08", "AW2-08PF20F", "AW2-08PF10F", "AW2-08PF3F", "Fe-3.5Si-4.5CrPF20F", "Fe-50NiPF20F", "Fe-80Ni-4MoPF20F" manufactured by EPSONATMIX Co., Ltd.; "LD-M", "LD-MH", "KNI-106", "KNI-206" manufactured by JFE Chemical Industries, Ltd. -106GSM", "KNI-106GS", "KNI-109", "KNI-109GSM", "KNI-109GS" manufactured by Toda Industry Co., Ltd.; "KNS-415", "BSF-547", "BSF-029", "BSN-125", "BSN-125", "BSN-714", "BSN-828", "S-1281", "S-1641", "S-1651", "S-1470", "S-1511", "S-2430" manufactured by Nippon Heavy Chemical Industry Co., Ltd.; "JR09P2" manufactured by CIK NanoTek Corporation; "Nanotek" manufactured by CIK NanoTek Corporation; "JEMK-S", "JEMK-H" manufactured by Kinsei Matek Co., Ltd.; "Yttrium iron oxide" manufactured by Aldrich Corporation, etc. The magnetic powder may be used alone or in combination of two or more.

[0060] (A) The magnetic powder is preferably spherical. The value (aspect ratio) obtained by dividing the major axis length of the magnetic powder by the minor axis length is preferably less than 2, more preferably less than 1.5, and further preferably less than 1.2. Generally speaking, when the magnetic powder is a non-spherical flat shape, it is easier to increase the relative magnetic permeability. However, in particular, when a spherical magnetic powder is used, magnetic loss can usually be reduced, and a paste with a preferred viscosity can be obtained, which is preferred based on this viewpoint.

[0061] From the viewpoint of improving relative magnetic permeability, the average particle size of the magnetic powder (A) is preferably 0.01 μm or more, more preferably 0.5 μm or more, further preferably 1 μm or more, and preferably 10 μm or less, more preferably 9 μm or less, further preferably 8 μm or less.

[0062] (A) The average particle size of the magnetic powder can be measured by a laser diffraction-scattering method based on Mie scattering theory. Specifically, a particle size distribution of the magnetic powder can be prepared on a volume basis using a laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The measured sample can preferably be a sample obtained by dispersing the magnetic powder in water using ultrasound. As a laser diffraction scattering particle size distribution measuring device, "LA-500" manufactured by Horiba, Ltd., "SALD-2200" manufactured by Shimadzu Corporation, etc. can be used.

[0063] From the viewpoint of improving the relative magnetic permeability, the specific surface area of ​​the magnetic powder (A) is preferably 0.05 m 2 / g or more, preferably 0.1 m 2 / g or more, more preferably 0.3 m 2 / g or more. In addition, preferably 10 m 2 / g or less, preferably 8m 2 / g or less, more preferably 5 m 2 (A) The specific surface area of ​​the magnetic powder can be measured by the BET method.

[0064] From the viewpoint of improving relative magnetic permeability and reducing loss factor, when the non-volatile component in the magnetic paste is set to 100 volume %, the content (volume %) of (A) magnetic powder is preferably 40 volume % or more, more preferably 50 volume % or more, and further preferably 60 volume % or more. In addition, it is preferably 85 volume % or less, more preferably 80 volume % or less, and further preferably 70 volume % or less.

[0065] From the viewpoint of improving relative magnetic permeability and reducing loss factor, when the non-volatile component in the magnetic paste is set to 100% by mass, the content (mass %) of (A) magnetic powder is preferably 70% by mass or more, more preferably 75% by mass or more, and further preferably 80% by mass or more. In addition, it is preferably 98% by mass or less, more preferably 95% by mass or less, and further preferably 90% by mass or less. It should be noted that in the present invention, unless otherwise expressly stated, the content of each component in the magnetic paste is the value when the non-volatile component in the magnetic paste is set to 100% by mass.

[0066] <(B) Epoxy resin>

[0067] The magnetic paste contains (B) epoxy resin as (B) component. Examples of (B) epoxy resin include: bisphenol A type epoxy resin; bisphenol F type epoxy resin; bisphenol S type epoxy resin; bisphenol AF type epoxy resin; dicyclopentadiene type epoxy resin; trisphenol type epoxy resin; phenol novolac type epoxy resin; tert-butyl catechol type epoxy resin; epoxy resins having a condensed ring structure such as naphthol novolac type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin; glycidylamine type epoxy resin; glycidyl ester type epoxy resin; cresol novolac type epoxy resin; biphenyl type epoxy resin; linear aliphatic epoxy resin; epoxy resin having a butadiene structure; alicyclic epoxy resin; heterocyclic epoxy resin; spiro ring-containing epoxy resin; cyclohexanedimethanol type epoxy resin; trimethylol type epoxy resin; tetraphenylethane type epoxy resin, etc. The epoxy resin may be used alone or in combination of two or more. The (B) epoxy resin is preferably at least one selected from bisphenol A epoxy resins and bisphenol F epoxy resins.

[0068] (B) epoxy resin is preferably an epoxy resin having more than 2 epoxy groups in one molecule. In addition, (B) epoxy resin preferably has an aromatic structure, and when using more than 2 epoxy resins, at least 1 has an aromatic structure. Aromatic structure refers to a chemical structure generally defined as aromatic, and also includes polycyclic aromatics and aromatic heterocycles. Relative to 100 mass % of the non-volatile component of epoxy resin, the ratio of epoxy resin having more than 2 epoxy groups in one molecule is preferably more than 50 mass %, more preferably more than 60 mass %, and particularly preferably more than 70 mass %.

[0069] Epoxy resins include epoxy resins that are liquid at 25° C. (hereinafter sometimes referred to as “liquid epoxy resins”) and epoxy resins that are solid at 25° C. (hereinafter sometimes referred to as “solid epoxy resins”). The magnetic paste may contain only a liquid epoxy resin or only a solid epoxy resin as (B) epoxy resin, but preferably contains a liquid epoxy resin from the viewpoint of reducing the viscosity of the magnetic paste.

[0070] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins having an ester skeleton, cyclohexanedimethanol type epoxy resins and epoxy resins having a butadiene structure, and more preferred are glycidyl amine type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins and naphthalene type epoxy resins. Specific examples of liquid epoxy resins include: "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL" (bisphenol A-type epoxy resins), "jER807" (bisphenol F-type epoxy resins), and "jER152" (phenol novolac-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" manufactured by Mitsubishi Chemical Corporation, and "EP-3980S" (glycidylamine-type epoxy resins) manufactured by ADEKA Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by Nippon Steel & Sumitomo Metal Chemicals Corporation; "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX Corporation; and "CELLOXIDE "ZX1658" and "ZX1658GS" (cyclic aliphatic diglycidyl ether (liquid 1,4-glycidylcyclohexane)) manufactured by Nippon Steel Chemical Co., Ltd., etc. These can be used alone or in combination of two or more.

[0071] As solid epoxy resins, preferred are naphthalene-type tetrafunctional epoxy resins, cresol novolac-type epoxy resins, dicyclopentadiene-type epoxy resins, trisphenol-type epoxy resins, naphthol-type epoxy resins, biphenyl-type epoxy resins, naphthylene ether-type epoxy resins, anthracene-type epoxy resins, bisphenol A-type epoxy resins, and tetraphenylethane-type epoxy resins; more preferred are naphthalene-type tetrafunctional epoxy resins, naphthol-type epoxy resins, and biphenyl-type epoxy resins. Specific examples of solid epoxy resins include: "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3 000H", "NC3000", "NC3000L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel & Sumitomo Chemical Corporation; "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bisxylenol type epoxy resin) and "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" (bisphenol AF type epoxy resin) and "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (solid bisphenol A type epoxy resin) and "jER1031S" (tetraphenylethane type epoxy resin) and the like. These may be used alone or in combination of two or more.

[0072] When the epoxy resin (B) is used in combination with a liquid epoxy resin and a solid epoxy resin, the amount ratio (liquid epoxy resin: solid epoxy resin) thereof is preferably in the range of 1:0.1 to 1:4 by mass ratio. By making the amount ratio of the liquid epoxy resin to the solid epoxy resin in such a range, an effect such as being able to obtain a cured product having sufficient fracture strength can be obtained. From the viewpoint of the above-mentioned effect, the amount ratio of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin: solid epoxy resin) is preferably in the range of 1:0.3 to 1:3.5 by mass ratio, further preferably in the range of 1:0.6 to 1:3, and particularly preferably in the range of 1:0.8 to 1:2.5.

[0073] From the viewpoint of obtaining a magnetic layer showing good mechanical strength, when the non-volatile component in the magnetic paste is set to 100% by mass, the content of (B) epoxy resin is preferably more than 1% by mass, more preferably more than 3% by mass, and further more preferably more than 5% by mass and more than 10% by mass. As long as the effect of the present invention is exerted, the upper limit of the content of epoxy resin is not particularly limited, preferably less than 30% by mass, more preferably less than 25% by mass, and further more preferably less than 20% by mass.

[0074] When the non-volatile component in the magnetic paste is set to 100% by volume, the content (volume %) of (B) epoxy resin is preferably more than 1% by volume, more preferably more than 3% by volume, and further more preferably more than 5% by volume. As long as the effect of the present invention is exerted, the upper limit is not particularly limited, preferably less than 25% by volume, more preferably less than 20% by volume, and further more preferably less than 15% by volume.

[0075] The epoxy equivalent of the epoxy resin (B) is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further preferably 110 g / eq. to 1000 g / eq.. By making it within this range, the crosslinking density of the cured product becomes sufficient, and a magnetic layer with a small surface roughness can be obtained. It should be noted that the epoxy equivalent can be measured in accordance with JIS K7236 and is the mass of a resin containing 1 equivalent of epoxy groups.

[0076] (B) The weight average molecular weight of the epoxy resin is preferably from 100 to 5000, more preferably from 250 to 3000, further preferably from 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0077] <(C) Acidic dispersant>

[0078] The magnetic paste contains (C) an acidic dispersant as the (C) component. As described above, the higher the content of the (A) magnetic powder, the higher the viscosity of the magnetic paste, and the worse the mechanical strength and the adhesion strength of the cured product of the magnetic paste. In the present invention, the magnetic paste contains the (C) acidic dispersant as a dispersant, so the viscosity can be lower than that of a paste not containing the (C) acidic dispersant (i.e., a paste having the same composition as the magnetic paste except that it does not contain the (C) component). Therefore, even if the content of the (A) magnetic powder is high, the increase in the viscosity of the magnetic paste can be suppressed, and the mechanical strength and the adhesion strength of the cured product of the magnetic paste can be improved. Generally, the (C) acidic dispersant as a dispersant is not volatile, so it will remain in the cured product obtained after curing.

[0079] In the present invention, (C) acidic dispersant means an acidic dispersant, and acidic means that the pH in the glass electrode method or the indicator method is lower than 6. That is, a dispersant with a pH lower than 6 in the glass electrode method or the indicator method is defined as an acidic dispersant. When both the glass electrode method and the indicator method can be used to measure pH, the pH measurement value of the glass electrode method is preferably used. The pH of the acidic dispersant can be measured by the glass electrode method using a pH detector and the indicator method using a pH test paper. In the specific pH measurement method using the glass electrode method, a measurement sample (22°C) with a dispersant concentration of 0.067 g / mL prepared by dissolving the acidic dispersant in a 30% by mass ethanol aqueous solution can be measured by using a pH meter with a glass electrode pH detector. In addition, in the specific pH measurement method using the indicator method, the measurement sample (22°C) with a dispersant concentration of 0.1 g / mL prepared by dissolving the acidic dispersant in acetone can be measured by soaking the pH test paper.

[0080] A commercially available pH tester can be used. Examples of commercially available pH testers include the pH tester "HM-41X" manufactured by DKK Co., Ltd. of East Asia. As pH test paper, a pH test paper that can measure pH in an acidic region (for example, a test paper having a measurement region of pH 0.0 to 14.0, pH 1.0 to 14.0, pH 0.5 to 5.0, etc.) can be used, such as the pH test paper "pH Test Paper pH 1 to 14" (pH measurement range pH 1.0 to 14.0) manufactured by AS ONE Co., Ltd.

[0081] As described above, when the pH of the acidic dispersant can be measured by both the glass electrode method and the indicator method, the pH of the acidic dispersant in the present invention is defined as the value measured by the glass electrode method. When the acidic dispersant cannot be measured by the glass electrode method for reasons such as the acidic dispersant is insoluble in a 30% by mass ethanol aqueous solution or a 30% by mass ethanol aqueous solution having a dispersant concentration of 0.067 g / mL cannot be prepared, the pH of the dispersant is defined as the pH by the indicator method.

[0082] The pH of the acidic dispersant (C) is preferably less than 4, more preferably at most 3.8, further preferably at most 3.5 or 3.3. The lower limit is preferably at least 2, more preferably at least 2.2, further preferably at least 2.4.

[0083] (C) The acidic dispersant includes an acidic dispersant that is liquid at 25° C. and an acidic dispersant that is solid at 25° C. From the viewpoint of further reducing the viscosity of the magnetic paste, the magnetic paste preferably contains a liquid acidic dispersant as (C) the acidic dispersant.

[0084] As the acidic dispersant (C), for example, an acidic surfactant of a suitable type can be used. The acidic dispersant (C) may have an acidic functional group such as a carboxyl group, a sulfo group, a phosphate group, etc. In addition, as the acidic dispersant (C), a polyether compound having a polyoxyalkylene chain, a polyether chain, etc. is preferred. As the acidic dispersant (C), a compound having a polyether chain and an acidic functional group is preferred.

[0085] (C) A commercially available acidic dispersant may be used. Specific examples thereof include: "C-2093I", "SC-1015F (a multifunctional comb-type functional polymer having an ionic group in the main chain and a polyoxyalkylene chain in the graft chain)" manufactured by NOF Corporation, "DA-375 (a polyether phosphate compound dispersant)" manufactured by Kusumoto Chemicals Co., Ltd.; "RS-410", "RS-610", and "RS-710" (pH 1.9) (a phosphate dispersant) of the "Phosphanol" series manufactured by Toho Chemical Industry Co., Ltd.; "AKM-0531", "AFB-1521", "SC-0505K", and "SC-0708A" of the "MALIALIM" series manufactured by NOF Corporation. (C) Acidic dispersants may be used alone or in combination of two or more.

[0086] From the viewpoint of significantly exerting the effect of the present invention, when the non-volatile component in the magnetic paste is set to 100 mass %, the content of the (C) acidic dispersant is preferably 0.1 mass % or more, more preferably 0.3 mass % or more, further preferably 0.5 mass % or more, and the upper limit is preferably 5 mass % or less, more preferably 4 mass % or less, further preferably 3 mass % or less.

[0087] When the mass of the (C) acidic dispersant when the nonvolatile components in the magnetic paste are 100 mass % is represented by C1, and the mass of the (A) magnetic powder when the nonvolatile components in the magnetic paste are 100 mass % is represented by A1, (C1 / A1)×100 is preferably at least 0.1, more preferably at least 0.5, further preferably at least 1, preferably at most 10, more preferably at most 5, further preferably at most 3. By adjusting the masses of the components (A) and (C) so that (C1 / A1)×100 is within the above range, the desired effect of the present invention can be more significantly obtained.

[0088] As preferred forms of (C) the acidic dispersant, the following examples can be cited:

[0089] That is, in one embodiment, (C) the acidic dispersant may be "RS-710" manufactured by Toho Chemical Industry Co., Ltd.;

[0090] Furthermore, in another embodiment, the (C) acidic dispersant may be an acidic dispersant other than "RS-710" manufactured by Toho Chemical Industry Co., Ltd.;

[0091] In yet another embodiment, (C) the acidic dispersant may be "RS-410", "RS-610", or "RS-710" manufactured by Toho Chemical Industry Co., Ltd.;

[0092] Furthermore, in yet another embodiment, the (C) acidic dispersant may be an acidic dispersant other than "RS-410", "RS-610", or "RS-710" manufactured by Toho Chemical Industry Co., Ltd.;

[0093] Furthermore, in yet another embodiment, (C) the acidic dispersant may be a phosphate dispersant;

[0094] Furthermore, in yet another embodiment, the (C) acidic dispersant may be an acidic dispersant other than a phosphate-based dispersant.

[0095] <(D) Curing agent>

[0096] The magnetic paste contains (D) a curing agent. The (D) curing agent includes: an epoxy resin curing agent having a function of curing the (B) epoxy resin, and a curing accelerator having a function of accelerating the curing speed of the (B) epoxy resin. The magnetic paste preferably contains an epoxy resin curing agent as the (D) curing agent. As the (D) curing agent, a curing accelerator may be included together with the epoxy resin curing agent. The curing accelerator is usually used together with the epoxy resin curing agent.

[0097] -Epoxy resin curing agent-

[0098] As the epoxy resin curing agent, for example, phenol epoxy resin curing agent, naphthol epoxy resin curing agent, active ester epoxy resin curing agent, anhydride epoxy resin curing agent, benzoxazine epoxy resin curing agent, cyanate epoxy resin curing agent, and imidazole epoxy resin curing agent can be cited. As the epoxy resin curing agent, from the viewpoint of reducing the viscosity of the magnetic paste, anhydride epoxy resin curing agent and imidazole epoxy resin curing agent are preferred, and further from the viewpoint of the mechanical strength of the obtained cured product, imidazole epoxy resin curing agent is more preferred. One epoxy resin curing agent can be used alone, or two or more can be used in combination.

[0099] As the phenolic epoxy resin curing agent and the naphthol epoxy resin curing agent, from the viewpoint of heat resistance and water resistance, a phenolic epoxy resin curing agent having a novolac structure or a naphthol epoxy resin curing agent having a novolac structure is preferred. As the phenolic epoxy resin curing agent, a nitrogen-containing phenolic epoxy resin curing agent is preferred, a phenolic epoxy resin curing agent containing a triazine skeleton is more preferred, and a phenol novolac epoxy resin curing agent containing a triazine skeleton is further preferred.

[0100] Specific examples of phenol-based epoxy resin curing agents and naphthol-based epoxy resin curing agents include: "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumitomo Chemicals Corporation, "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by DIC Corporation, and "GDP-6115L" and "GDP-6115H" manufactured by Gunei Chemical Co., Ltd.

[0101] As active ester epoxy resin curing agent, there is no particular limitation, and generally preferably used are compounds having ester groups with more than two high reactive activities in one molecule, such as phenolic esters, thiophenolic esters, N-hydroxylamine esters, and esters of heterocyclic hydroxy compounds. The active ester epoxy resin curing agent is preferably a compound obtained by the condensation reaction of a carboxylic acid compound and / or a thiocarboxylic acid compound with a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improved heat resistance, it is preferably an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a hydroxy compound, and more preferably an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound. As carboxylic acid compounds, for example: benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol with one molecule of dicyclopentadiene.

[0102] Specifically, active ester epoxy resin curing agents containing dicyclopentadiene diphenol structure, active ester epoxy resin curing agents containing naphthalene structure, active ester epoxy resin curing agents containing acetylated products of phenol novolac resin, and active ester epoxy resin curing agents containing benzoylated products of phenol novolac resin are preferred. "Dicyclopentadiene diphenol structure" means a divalent structure formed by phenylene-dicyclopentylene (dicyclopentylene)-phenylene.

[0103] Commercially available active ester epoxy resin curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" manufactured by DIC Corporation as active ester epoxy resin curing agents containing a dicyclopentadiene-type diphenol structure; and active ester compounds containing a naphthalene structure, Examples include "EXB9416-70BK" manufactured by DIC Corporation; as an active ester epoxy resin curing agent containing an acetylated product of a phenol novolac resin, there can be mentioned "DC808" manufactured by Mitsubishi Chemical Corporation; as an active ester epoxy resin curing agent containing a benzoylated product of a phenol novolac resin, there can be mentioned "YLH1026", "YLH1030", and "YLH1048" manufactured by Mitsubishi Chemical Corporation; and the like.

[0104] Examples of the acid anhydride epoxy resin curing agent include epoxy resin curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride epoxy resin curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and tetrahydrophthalic anhydride. Formic anhydride, benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, and the like polymer type acid anhydrides, etc.

[0105] Examples of commercially available products of anhydride-based epoxy resin curing agents include "HNA-100" and "MH-700" manufactured by Shin Nippon Rika Co., Ltd.

[0106] Specific examples of the benzoxazine-based epoxy resin curing agent include "HFB2006M" manufactured by Showa Highpolymer Co., Ltd. and "Pd" and "Fa" manufactured by Shikoku Chemicals Co., Ltd.

[0107] Examples of cyanate epoxy resin curing agents include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinizing a portion of these cyanate resins. Specific examples of cyanate ester epoxy resin curing agents include "PT30" and "PT60" manufactured by Lonza Japan Co., Ltd. (both are phenol novolac-type multifunctional cyanate resins), "BA230", and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to form a trimer), etc.

[0108] Examples of the imidazole epoxy resin curing agent include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4 imidazole compounds such as -diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, isocyanuric acid adduct of 2-phenylimidazole, isocyanuric acid adduct of 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole.

[0109] As the imidazole epoxy resin curing agent, a commercially available product can be used, and examples thereof include "2MZA-PW" and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd. and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0110] The amount ratio of epoxy resin to epoxy resin curing agent is preferably in the range of 1:0.2 to 1:2, more preferably in the range of 1:0.3 to 1:1.5, and further preferably in the range of 1:0.4 to 1:1. Here, the reactive group of epoxy resin curing agent refers to active hydroxyl group, active ester group, etc., which varies according to the type of epoxy resin curing agent. In addition, the total number of epoxy groups of epoxy resin refers to the value obtained by summing up the value obtained by dividing the non-volatile component mass of each epoxy resin by the epoxy equivalent for all epoxy resins, and the total number of reactive groups of epoxy resin curing agent refers to the value obtained by summing up the value obtained by dividing the non-volatile component mass of each epoxy resin curing agent by the reactive group equivalent for all epoxy resin curing agents. By making the amount ratio of epoxy resin to epoxy resin curing agent within such a range, the heat resistance when formed into a cured product is further improved.

[0111] - Curing accelerator -

[0112] As a curing accelerator, for example, an amine curing accelerator, an imidazole curing accelerator, a phosphorus curing accelerator, a guanidine curing accelerator, a metal curing accelerator, etc. can be cited. From the viewpoint of reducing the concentration of the magnetic paste, the curing accelerator is preferably an amine curing accelerator, an imidazole curing accelerator, and a guanidine curing accelerator, and further from the viewpoint of improving the mechanical strength of the obtained cured product, an imidazole curing accelerator is more preferably used. One curing accelerator can be used alone, or two or more can be used in combination. A curing accelerator can generally be used together with an epoxy resin curing agent.

[0113] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo[5.4.0]undecene, and 4-dimethylaminopyridine and 1,8-diazabicyclo[5.4.0]undecene are preferred.

[0114] As the amine curing accelerator, a commercially available product may be used, and examples thereof include "PN-50", "PN-23", and "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0115] The imidazole curing accelerator is the same as the above-mentioned imidazole epoxy resin curing agent. The above-mentioned imidazole epoxy resin curing agent may be used together with other epoxy resin curing agents or may function as a curing accelerator.

[0116] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate. Triphenylphosphine and tetrabutylphosphonium decanoate are preferred.

[0117] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine and 1-(o-tolyl)biguanidine, and dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0118] As metal curing accelerators, for example, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II), cobalt acetylacetonate (III), organic copper complexes such as copper acetylacetonate (II), organic zinc complexes such as zinc acetylacetonate (II), organic iron complexes such as iron acetylacetonate (III), organic nickel complexes such as nickel acetylacetonate (II), and organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octoate, tin octoate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.

[0119] When the non-volatile component in the magnetic paste is set to 100 mass %, from the viewpoint of reducing the viscosity of the magnetic paste and increasing the service life of the viscosity, when the resin component in the magnetic paste is set to 100 mass %, the content of the (D) curing agent is preferably 0.1 mass % or more, more preferably 0.3 mass % or more, further preferably 0.5 mass % or more, and the upper limit is preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 1 mass % or less.

[0120] When the mass of the (D) curing agent when the non-volatile components in the magnetic paste are 100 mass % is defined as D1, and the mass of the (C) acidic dispersant when the non-volatile components in the magnetic paste are 100 mass % is defined as C1, C1 / D1 is preferably 0.1 or more, more preferably 0.5 or more, further preferably 1 or more, preferably 10 or less, more preferably 5 or less, further preferably 3 or less. By adjusting the masses of the components (C) and (D) so that C1 / D1 is within the above range, the desired effect of the present invention can be more significantly obtained.

[0121] When the mass of the (A) magnetic powder when the non-volatile component in the magnetic paste is 100 mass % is A1, the mass of the (B) epoxy resin when the non-volatile component in the magnetic paste is 100 mass % is B1, the mass of the (C) acidic dispersant when the non-volatile component in the magnetic paste is 100 mass % is C1, and the mass of the (D) curing agent when the non-volatile component in the magnetic paste is 100 mass % is D1, (B1+C1+D1) / A1 is preferably 0.01 or more, more preferably 0.05 or more, further preferably 0.1 or more, preferably 1 or less, more preferably 0.5 or less, further preferably 0.3 or less. By adjusting the mass of the (A) component to the (D) component so that (B1+C1+D1) / A1 is within the above range, the desired effect of the present invention can be more significantly obtained.

[0122] When the mass of the (A) magnetic powder when the non-volatile component in the magnetic paste is 100 mass % is A1, the mass of the (C) acidic dispersant when the non-volatile component in the magnetic paste is 100 mass % is C1, and the mass of the (D) curing agent when the non-volatile component in the magnetic paste is 100 mass % is D1, ((C1+D1) / A1)×100 is preferably 0.1 or more, more preferably 0.5 or more, further preferably 1 or more, preferably 10 or less, more preferably 5 or less, further preferably 3 or less. By adjusting the masses of the components (A), (C) and (D) so that ((C1+D1) / A1)×100 is within the above range, the desired effect of the present invention can be more significantly obtained.

[0123] <(E) Other additives>

[0124] The magnetic paste may further contain (E) other additives as required. Examples of such other additives include: curing retardants such as triethyl borate; inorganic fillers (however, excluding materials belonging to the magnetic powder); thermoplastic resins; flame retardants; organic fillers; organic metal compounds such as organic copper compounds, organic zinc compounds and organic cobalt compounds; as well as thickeners; defoamers; leveling agents; adhesion-imparting agents; and resin additives such as colorants.

[0125] The content of the organic solvent contained in the above-mentioned magnetic paste is preferably less than 1.0% by mass, more preferably less than 0.8% by mass, further preferably less than 0.5% by mass, and particularly preferably less than 0.1% by mass relative to the total mass of the magnetic paste. The lower limit is not particularly limited, and is 0.001% by mass or more, or does not contain an organic solvent. For the magnetic paste, the viscosity thereof can be reduced even if it does not contain an organic solvent. Since the amount of organic solvent in the magnetic paste is small, the generation of pores due to the volatilization of the organic solvent can be suppressed.

[0126] In addition, the magnetic paste may contain anionic dispersants such as sodium dodecylbenzene sulfonate, sodium laurate, and ammonium salts of polyoxyethylene alkyl ether sulfates; nonionic dispersants such as organosiloxane dispersants, acethylene glycol, polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, and polyoxyethylene alkylamides, or may not contain them. As organosiloxane dispersants, commercially available products include BYK-Chemie's "BYK347" and "BYK348". As polyoxyalkylene dispersants, commercially available products include NOF Corporation's "HKM-50A" and "HKM-150A". The so-called polyoxyalkylene dispersant is a general term for polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene alkylamides, etc. As acetylene glycol, commercially available products include "82", "104", "440", "465" and "485" of the "Surfynol" series manufactured by Air Products and Chemicals Inc., and "Olefin Y" and the like.

[0127] In one embodiment, the magnetic paste may include magnetic powder, an organized layered silicate mineral, and a binder resin. In addition, in another embodiment, the magnetic paste may not include "a magnetic paste including magnetic powder, an organized layered silicate mineral, and a binder resin" (i.e., "a magnetic paste including magnetic powder, an organized layered silicate mineral, and a binder resin" is excluded). The details of the magnetic powder, the organized layered silicate mineral, and the binder resin that may be included in the magnetic paste according to these embodiments can be referred to the records of Japanese Patent Application No. 2018-139537.

[0128] For the magnetic paste, in one embodiment, it may include: magnetic powder with an average particle size of 1 μm or more, epoxy resin, reactive diluent, curing agent, and filler with an average particle size of less than 1 μm. In addition, for the magnetic paste, in another embodiment, "a magnetic paste containing magnetic powder with an average particle size of 1 μm or more, epoxy resin, reactive diluent, curing agent, and filler with an average particle size of less than 1 μm" may not be included. For details of the magnetic powder with an average particle size of 1 μm or more, epoxy resin, reactive diluent, curing agent, and filler with an average particle size of less than 1 μm that the magnetic paste involved in these embodiments may contain, please refer to the records of Japanese Patent Application No. 2018-219667.

[0129] <Method for producing magnetic paste>

[0130] The magnetic paste can be produced, for example, by stirring the mixed components with a stirring device such as a three-roll mill or a rotary mixer.

[0131] <Physical properties of magnetic paste>

[0132] The magnetic paste has a low viscosity. Therefore, the magnetic paste has excellent printability. The viscosity at 25°C is preferably 200 Pa・s or less, more preferably 150 Pa・s or less, further preferably less than 100 Pa・s, preferably 10 Pa・s or more, more preferably 20 Pa・s or more, further preferably 30 Pa・s or more. The viscosity can be measured, for example, using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., RE-80U), and in detail, can be measured by the method described in the examples described later.

[0133] The magnetic paste generally shows a property that the viscosity increases over time. Specifically, the viscosity of the magnetic paste at 25°C after being left for one week is preferably 200 Pa・s or less, more preferably 180 Pa・s or less, further preferably 150 Pa・s or less and less than 100 Pa・s, preferably 30 Pa・s or more, more preferably 40 Pa・s or more, further preferably 50 Pa・s or more. The viscosity of the magnetic paste after being left for one week can be measured, for example, using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., RE-80U), and in detail, can be measured by the method described in the examples described later.

[0134] The cured product obtained by heating the magnetic paste at 180° C. for 90 minutes shows excellent mechanical strength (tensile strength at break). Therefore, the cured product brings a magnetic layer with excellent tensile strength at break. As the tensile strength at break, it is preferably 40 MPa or more, more preferably 45 MPa or more, and further preferably 50 MPa or more. The upper limit is not particularly limited and can be set to 100 MPa or less. The tensile strength at break can be measured by the method described in the embodiments described later.

[0135] The solidified material obtained by heating the magnetic paste at 180°C for 90 minutes shows excellent properties of the coating adhesion between the coating. Therefore, the aforementioned solidified material brings a magnetic layer with excellent adhesion strength between the coating. As the adhesion strength representing the coating adhesion, it is preferably more than 0.2 kgf / cm, more preferably more than 0.21 kgf / cm, and further more preferably more than 0.22 kgf / cm. The upper limit is not particularly limited, and can be set to less than 10 kgf / cm, etc. The adhesion strength can be measured by the method described in the embodiments described later.

[0136] The cured product obtained by heating the magnetic paste at 180° C. for 90 minutes generally exhibits a high relative permeability at a frequency of 100 MHz. Therefore, the cured product provides a magnetic layer with a high relative permeability. The relative permeability of the cured product at a frequency of 100 MHz is preferably 1 or more, more preferably 2 or more, and further preferably 4 or more. In addition, the upper limit is not particularly limited and can be set to 20 or less.

[0137] The cured product obtained by heating the magnetic paste at 180° C. for 90 minutes generally exhibits the characteristic of low magnetic loss at a frequency of 100 MHz. Therefore, the cured product provides a magnetic layer with low magnetic loss. The magnetic loss of the cured product at a frequency of 100 MHz is preferably 1 or less, more preferably 0.9 or less, and further preferably 0.8 or less. The lower limit is not particularly limited and can be set to 0.001 or more.

[0138] [cured material]

[0139] The cured product of the present invention is obtained by curing the magnetic paste of the present invention. The curing conditions of the magnetic paste may be the conditions of step (2) described later. In addition, the magnetic paste may be preheated before thermally curing, and the heating including preheating may be performed multiple times.

[0140] [Magnetic Sheet]

[0141] The magnetic sheet includes a support and a resin composition layer formed of a magnetic paste and provided on the support.

[0142] From the viewpoint of thinning, the thickness of the resin composition layer is preferably at most 250 μm, more preferably at most 200 μm, further preferably at most 150 μm or at most 100 μm. The lower limit of the thickness of the resin composition layer is not particularly limited, but is usually at least 5 μm.

[0143] Examples of the support include films formed of a plastic material, metal foil and release paper, and films formed of a plastic material and metal foil are preferred.

[0144] When a film formed of a plastic material is used as a support, the plastic material includes, for example, polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0145] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. As the copper foil, a foil formed of a single metal of copper can be used, or a foil formed of an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used.

[0146] The surface of the support to be in contact with the resin composition layer may be subjected to matte treatment or corona treatment.

[0147] In addition, as a support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As a release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins can be cited. The support with a release layer can use commercially available products, for example: "SK-1", "AL-5", and "AL-7" manufactured by Lintec Co., Ltd., which are PET films having a release layer with an alkyd resin release agent as a main component; "Lumirror T60" manufactured by Toray Industries, Ltd.; "Purex" manufactured by Teijin Limited; "Unipeel" manufactured by UNITIKA Co., Ltd., etc.

[0148] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the entire thickness of the support with a release layer is preferably within the above range.

[0149] The magnetic sheet can be produced, for example, by preparing a resin varnish obtained by dissolving a magnetic paste in an organic solvent, applying the resin varnish on a support using a die coater, and then drying the varnish to form a resin composition layer. It should be noted that the magnetic sheet can also be produced by directly applying the magnetic paste on a support using a die coater to form a resin composition layer.

[0150] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (MEK) and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate (cellosolve acetate), propylene glycol monomethyl ether acetate and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aromatic hydrocarbons such as toluene and xylene; amide solvents such as dimethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone, etc. The organic solvent may be used alone or in combination of two or more.

[0151] Drying can be carried out by known methods such as heating and hot air blowing. The drying conditions are not particularly limited, and the drying is carried out under the condition that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin varnish. For example, in the case of using a resin varnish containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.

[0152] In the magnetic sheet, a protective film selected according to the support can be further laminated on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support). The thickness of the protective film is not particularly limited, and is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to prevent the surface of the resin composition layer from being attached to garbage or being damaged. The magnetic sheet can be rolled up and stored. In the case where the magnetic sheet has a protective film, it can be used by peeling off the protective film.

[0153] [Circuit board and method for manufacturing the same]

[0154] The circuit substrate of the first embodiment includes: a substrate having a through hole, and a cured product of the magnetic paste of the present invention filled in the through hole. In addition, the circuit substrate of the second embodiment includes: a magnetic layer formed by a cured product of a resin composition layer of a magnetic sheet. The first and second embodiments of the method for manufacturing a circuit substrate are described below. However, the method for manufacturing a circuit substrate according to the present invention is not limited to the first and second embodiments exemplified below.

[0155] <First embodiment>

[0156] The circuit board of the first embodiment can be produced, for example, by a production method including the following steps (1) to (4). In the first embodiment, it is preferred to form the magnetic layer using a magnetic paste. The production method includes:

[0157] (1) a step of filling a through-hole of a substrate having a through-hole with a magnetic paste;

[0158] (2) a step of thermally curing the magnetic paste to obtain a cured product;

[0159] (3) a step of grinding the surface of the solidified material or the magnetic paste; and

[0160] (4) forming a conductive layer on the polished surface of the cured product,

[0161] The method for producing a circuit board of the present invention may be performed in the order of steps (1) to (4), or the step (2) may be performed after the step (3).

[0162] Hereinafter, the above-mentioned steps (1) to (4) in manufacturing the circuit board will be described in detail.

[0163] <Process (1)>

[0164] When performing step (1), a step of preparing a magnetic paste may be included. The magnetic paste is as described above.

[0165] In addition, when performing step (1), if Figure 1 As shown in the example, the process of preparing a core substrate 10 may include: a support substrate 11, and a first metal layer 12 and a second metal layer 13 formed of a metal such as copper foil provided on both surfaces of the support substrate 11. Examples of the material of the support substrate 11 include insulating substrates such as glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. Examples of the material of the first metal layer and the second metal layer include copper foil with a carrier, the material of the conductor layer described later, and the like.

[0166] In addition, if Figure 2 As shown in the example, the process of forming the through hole 14 in the core substrate 10 may be included. The through hole 14 may be formed, for example, by a drill, laser irradiation, plasma irradiation, etc. Specifically, the through hole 14 may be formed by forming a through hole in the core substrate 10 using a drill or the like.

[0167] The through hole 14 can be formed using a commercially available drill device. Examples of commercially available drill devices include "ND-1S211" manufactured by Hitachi Via Machine Co., Ltd.

[0168] After the through hole 14 is formed in the core substrate 10, Figure 3 As shown in the example of FIG. 1 , the process may include roughening the core substrate 10 and forming the plating layer 20 in the through hole 14 , on the surface of the first metal layer 12 , and on the surface of the second metal layer 13 .

[0169] As the aforementioned roughening treatment, any of dry and wet roughening treatments may be performed. Examples of dry roughening treatments include plasma treatment and the like. In addition, examples of wet roughening treatments include a method of sequentially performing swelling treatment using a swelling solution, roughening treatment using an oxidizing agent, and neutralization treatment using a neutralizing solution.

[0170] The plated layer 20 can be formed by a plating method. The procedure for forming the plated layer 20 by a plating method is the same as the formation of the conductor layer in step (4) described later.

[0171] After the core substrate 10 having the plating layer 20 formed in the through hole 14 is prepared, Figure 4 As shown in the example, the magnetic paste 30a is filled into the through hole 14. Examples of the filling method include a method of filling the magnetic paste 30a into the through hole 14 via a squeegee, a method of filling the magnetic paste 30a via a cartridge, a method of filling the magnetic paste 30a by mask printing, a roller coating method, an inkjet method, and the like.

[0172] <Process (2)>

[0173] In step (2), after the magnetic paste 30a is filled into the through hole 14, the magnetic paste 30 is thermally cured. Figure 5 As shown in the example, a cured material layer (magnetic layer) 30 is formed in the through hole 14. The heat curing conditions of the magnetic paste 30a vary depending on the composition or type of the magnetic paste 30a, and the curing temperature is preferably 120°C or more, more preferably 130°C or more, further preferably 150°C or more, preferably 240°C or less, more preferably 220°C or less, and further preferably 200°C or less. The curing time of the magnetic paste 30a is preferably 5 minutes or more, more preferably 10 minutes or more, further preferably 15 minutes or more, preferably 120 minutes or less, more preferably 100 minutes or less, and further preferably 90 minutes or less.

[0174] The degree of curing of the magnetic layer 30 in the step (2) is preferably at least 80%, more preferably at least 85%, further preferably at least 90%. The degree of curing can be measured using, for example, a differential scanning calorimeter.

[0175] Before the magnetic paste 30a is thermally cured, the magnetic paste 30a may be subjected to a preheating treatment of heating at a temperature lower than the curing temperature. For example, before the magnetic paste 30a is thermally cured, the magnetic paste 30a may be preheated at a temperature of usually 50°C or more and less than 120°C, preferably 60°C or more and 110°C or less, and more preferably 70°C or more and 100°C or less, for usually 5 minutes or more, preferably 5 minutes to 150 minutes, and more preferably 15 minutes to 120 minutes.

[0176] <Step (3)>

[0177] In step (3), if Figure 6 As shown in the example of FIG, the excess magnetic layer 30 protruding from or attached to the core substrate 10 is removed by grinding to flatten. As a grinding method, a method that can grind the excess magnetic layer 30 protruding from or attached to the core substrate 10 can be used. As such a grinding method, for example, polishing grinding, belt grinding, etc. can be cited. As a commercially available polishing grinding device, "NT-700IM" manufactured by Ishii Hyoki Co., Ltd. can be cited.

[0178] As the arithmetic mean roughness (Ra) of the polished surface of the magnetic layer, from the viewpoint of improving the adhesion of the coating, it is preferably more than 300 nm, more preferably more than 350 nm, and further more preferably more than 400 nm. The upper limit is preferably less than 1000 nm, more preferably less than 900 nm, and further more preferably less than 800 nm. The surface roughness (Ra) can be measured using a non-contact surface roughness meter, for example.

[0179] When step (3) is performed after step (2), heat treatment may be performed after step (2) and before step (3) as necessary for the purpose of further improving the curing degree of the magnetic layer, etc. The temperature in the heat treatment may be the above-mentioned curing temperature, preferably 120°C or more, more preferably 130°C or more, further preferably 150°C or more, preferably 240°C or less, more preferably 220°C or less, further preferably 200°C or less. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, further preferably 15 minutes or more, preferably 90 minutes or less, more preferably 70 minutes or less, further preferably 60 minutes or less.

[0180] In addition, when step (3) is performed before step (2), a preheating treatment of heating at a temperature lower than the curing temperature of the magnetic paste may be performed before step (3). The temperature in the preheating treatment is preferably 100° C. or higher, more preferably 110° C. or higher, further preferably 120° C. or higher, preferably 240° C. or lower, more preferably 220° C. or lower, further preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or higher, more preferably 10 minutes or higher, further preferably 15 minutes or higher, preferably 90 minutes or lower, more preferably 70 minutes or lower, further preferably 60 minutes or lower.

[0181] <Step (4)>

[0182] In step (4), if Figure 7 As shown in the example, the conductor layer 40 is formed on the polished surface of the magnetic layer 30 and the plated layer 20. After the conductor layer 40 is formed, Figure 8 As shown in the example, the conductor layer 40, the first metal layer 12, the second metal layer 13, and a portion of the plating layer 20 can be removed by etching or the like to form a pattern conductor layer 41. In the present invention, the solidified material is polished in step (3), and therefore, the step of roughening the magnetic layer is not included. Figure 7 In the embodiment, the conductor layer 40 is formed on both surfaces of the core substrate 10 , but the conductor layer 40 may be formed only on one surface of the core substrate 10 .

[0183] Regarding the method for forming the conductor layer, for example, plating method, sputtering method, evaporation method, etc. can be cited, among which plating method is preferred. In a preferred embodiment, the surface of the solidified material is plated by an appropriate method such as a semi-additive method and a full-additive method to form a pattern conductor layer having a desired wiring pattern. As the material of the conductor layer, for example, single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium can be cited; alloys of two or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among them, from the viewpoints of versatility, cost, ease of patterning, etc., it is preferred to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or nickel-chromium alloy, copper-nickel alloy, copper-titanium alloy, more preferably chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or nickel-chromium alloy, and further preferably copper.

[0184] Here, an example of an implementation method for forming a pattern conductor layer on the polished surface of a solidified object is described in detail. A plating seed layer is formed on the polished surface of the solidified object by electroless plating. Next, an electrolytic plating layer is formed on the formed plating seed layer by electrolytic plating, and the unnecessary plating seed layer is removed by etching or the like as needed, thereby forming a conductor layer having a desired wiring pattern. After the conductor layer is formed, an annealing treatment may be performed as needed in order to improve the peel strength of the conductor layer, etc. The annealing treatment may be performed, for example, by heating the circuit substrate at 150 to 200° C. for 20 to 90 minutes.

[0185] From the viewpoint of thinning, the thickness of the pattern conductor layer is preferably below 70 μm, more preferably below 60 μm, further preferably below 50 μm, further preferably below 40 μm, particularly preferably below 30 μm, below 20 μm, below 15 μm or below 10 μm. The lower limit is preferably above 1 μm, more preferably above 3 μm, and further preferably above 5 μm.

[0186] <Second embodiment>

[0187] The circuit substrate of the second embodiment includes a magnetic layer formed by a cured product of a magnetic paste. In the second embodiment, it is preferred to use a magnetic sheet to form the magnetic layer. Hereinafter, the second embodiment of the method for manufacturing the circuit substrate will be described. The description of the parts that overlap with the description of the first embodiment will be appropriately omitted.

[0188] The circuit board of the second embodiment can be manufactured, for example, by a manufacturing method including the following steps (A) to (D). The manufacturing method includes:

[0189] (A) a step of laminating a magnetic sheet on an inner substrate so that the resin composition layer is bonded to the inner substrate to form a magnetic layer,

[0190] (B) a step of drilling holes in the magnetic layer,

[0191] (C) a step of polishing the surface of the magnetic layer, and

[0192] (D) A step of forming a conductive layer on the polished surface of the magnetic layer.

[0193] Hereinafter, the above-mentioned steps (A) to (D) in manufacturing the circuit board will be described in detail.

[0194] <Process (A)>

[0195] Step (A) is a step of laminating a magnetic sheet on an inner substrate in such a manner that the resin composition layer is bonded to the inner substrate to form a magnetic layer. As one embodiment of step (A), a magnetic sheet is laminated on an inner substrate in such a manner that the resin composition layer is bonded to the inner substrate, and the resin composition layer is thermally cured to form a magnetic layer.

[0196] In step (A), if Fig. 9 As shown in one example, the magnetic sheet 310 including the support 330 and the resin composition layer 320 a provided on the support 330 is stacked on the inner substrate 200 so that the resin composition layer 320 a is bonded to the inner substrate 200 .

[0197] The inner substrate 200 is an insulating substrate. Examples of the material of the inner substrate 200 include insulating substrates such as glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates. The inner substrate 200 may be an inner circuit substrate having wiring and the like built into its thickness.

[0198] like Fig. 9 As shown in the example, the inner substrate 200 has: a first conductor layer 420 provided on the first main surface 200a, and an external terminal 240 provided on the second main surface 200b. The first conductor layer 420 may include a plurality of wirings. In the example shown in the figure, only the wiring of the coil-shaped conductive structure 400 constituting the inductor element is shown. The external terminal 240 is a terminal for electrically connecting to an external device, etc., which is not shown. The external terminal 240 may be configured as a part of the conductor layer provided on the second main surface 200b.

[0199] The conductive material that can constitute the first conductive layer 420 and the external terminal 240 is the same as the material of the conductive layer described in the column “<Step (4)>” of the first embodiment.

[0200] The first conductor layer 420 and the external terminal 240 may be a single-layer structure or a multilayer structure formed by stacking two or more single metal layers or alloy layers formed by different types of metals or alloys. In addition, the thickness of the first conductor layer 420 and the external terminal 240 is the same as that of the second conductor layer 440 described later.

[0201] The line width (L) / line spacing (S) ratio of the first conductor layer 420 and the external terminal 240 is not particularly limited. From the perspective of reducing surface unevenness and obtaining a magnetic layer with excellent smoothness, it is usually 900 / 900 μm or less, preferably 700 / 700 μm or less, more preferably 500 / 500 μm or less, further preferably 300 / 300 μm or less, and further preferably 200 / 200 μm or less. The lower limit of the line width / line spacing ratio is not particularly limited. From the perspective of making the resin composition layer fill the wiring interval well, it is preferably 1 / 1 μm or more.

[0202] The inner substrate 200 may have a plurality of through holes 220 penetrating the inner substrate 200 from the first main surface 200a to the second main surface 200b. Through-hole wiring 220a is provided in the through hole 220. The through-hole wiring 220a electrically connects the first conductor layer 420 and the external terminal 240.

[0203] The resin composition layer 320a and the inner substrate 200 can be bonded, for example, by heat-pressing the magnetic sheet 310 to the inner substrate 200 from the support 330 side. As a member for heat-pressing the magnetic sheet 310 to the inner substrate 200 (hereinafter also referred to as a "heat-pressing member"), for example, a heated metal plate (stainless steel (SUS) end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that it is preferred that the heat-pressing member is not pressed in direct contact with the magnetic sheet 310, but is pressed through a sheet formed of an elastic material such as heat-resistant rubber, so that the magnetic sheet 310 fully follows the surface unevenness of the inner substrate 200.

[0204] The temperature during heat pressing is preferably in the range of 80°C to 160°C, more preferably 90°C to 140°C, and further preferably 100°C to 120°C, the pressure during heat pressing is preferably in the range of 0.098 MPa to 1.77 MPa, and more preferably 0.29 MPa to 1.47 MPa, and the time during heat pressing is preferably in the range of 20 seconds to 400 seconds, and more preferably 30 seconds to 300 seconds. The bonding of the magnetic sheet and the inner substrate is preferably carried out under reduced pressure conditions of 26.7 hPa or less.

[0205] The resin composition layer 320a of the magnetic sheet 310 and the inner substrate 200 can be bonded using a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressurized laminator manufactured by Meiki Mfg. Co., Ltd. and a vacuum applicator manufactured by Nikko-Materials Co., Ltd.

[0206] After the magnetic sheet 310 is bonded to the inner substrate 200, the laminated magnetic sheet 310 can be smoothed by pressing the heating and pressing member under normal pressure (under atmospheric pressure), for example, from the support body side. The pressing conditions for the smoothing treatment can be set to the same conditions as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and the smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.

[0207] After laminating the magnetic sheet on the inner substrate, the resin composition layer is thermally cured to form a magnetic layer. Fig.10 As in the example shown in FIG. 2 , the resin composition layer 320 a bonded to the inner substrate 200 is thermally cured to form the first magnetic layer 320 .

[0208] The heat curing conditions of the resin composition layer 320a vary depending on the composition or type of the resin composition, and the curing temperature is preferably 120°C or more, more preferably 130°C or more, further preferably 150°C or more, preferably 240°C or less, more preferably 220°C or less, and further preferably 200°C or less. The curing time of the resin composition layer 320a is preferably 5 minutes or more, more preferably 10 minutes or more, further preferably 15 minutes or more, preferably 120 minutes or less, more preferably 100 minutes or less, and further preferably 90 minutes or less.

[0209] The support body 330 may be removed after the thermal curing in step (A) and between step (B), or may be peeled off after step (B).

[0210] <Process (B)>

[0211] In step (B), if Fig.11 As shown in the example of FIG, the first magnetic layer 320 is subjected to a hole-opening process to form a via hole 360. The via hole 360 ​​becomes a path for electrically connecting the first conductor layer 420 to the second conductor layer 440 described later. The formation of the via hole 360 ​​can be implemented using, for example, a drill, a laser, a plasma, etc., depending on the composition of the resin composition used in the formation of the magnetic layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.

[0212] <Process (C)>

[0213] In step (C), the surface of the magnetic layer having the through holes formed therein is polished. The polishing method in step (C) can be performed by the same polishing method as described in the column "<Step (3)>" of the first embodiment.

[0214] As the arithmetic mean roughness (Ra) of the polished surface of the magnetic layer, from the viewpoint of improving the adhesion of the coating, it is preferably more than 300 nm, more preferably more than 350 nm, and further more preferably more than 400 nm. The upper limit is preferably less than 1000 nm, more preferably less than 900 nm, and further more preferably less than 800 nm. The surface roughness (Ra) can be measured using a non-contact surface roughness meter, for example.

[0215] <Process (D)>

[0216] In step (D), if Fig.12 As in the example shown in FIG. 4 , the second conductor layer 440 is formed on the first magnetic layer 320 .

[0217] The conductive material that can constitute the second conductive layer 440 is the same as the material of the conductive layer described in the column “<Step (4)>” of the first embodiment.

[0218] From the viewpoint of thinning, the thickness of the second conductor layer 440 is preferably 70 μm or less, more preferably 60 μm or less, further preferably 50 μm or less, further preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and further preferably 5 μm or more.

[0219] The second conductor layer 440 can be formed by plating. The second conductor layer 440 is preferably formed by a wet plating method such as a semi-additive method or a full-additive method including an electroless plating step, a mask pattern forming step, an electrolytic plating step, and a flash etching step. By forming the second conductor layer 440 by the wet plating method, it is possible to form the second conductor layer 440 including a desired wiring pattern. It should be noted that, by this process, the through-hole wiring 360a can be formed in the through-hole 360 ​​at the same time.

[0220] For the first conductor layer 420 and the second conductor layer 440, for example, as described later Figures 13-15 As shown in the example, it can be set in a spiral shape. In one example, one end on the central side of the spiral wiring portion of the second conductor layer 440 is electrically connected to one end on the central side of the spiral wiring portion of the first conductor layer 420 through the through-hole wiring 360a. The other end on the outer peripheral side of the spiral wiring portion of the second conductor layer 440 is electrically connected to the land 420a of the first conductor layer 420 through the through-hole wiring 360a. Therefore, the other end on the outer peripheral side of the spiral wiring portion of the second conductor layer 440 is electrically connected to the external terminal 240 via the through-hole wiring 360a, the land 420a, and the through-hole wiring 220a.

[0221] The coil-shaped conductive structure 400 is composed of a spiral wiring portion as a part of the first conductor layer 420, a spiral wiring portion as a part of the second conductor layer 440, and a through-hole wiring 360a that electrically connects the spiral wiring portion of the first conductor layer 420 and the spiral wiring portion of the second conductor layer 440.

[0222] After step (D), a step of forming a magnetic layer on the conductor layer may be further performed. Fig.14 As shown in the example of FIG. 3 , the second magnetic layer 340 is formed on the first magnetic layer 320 on which the second conductor layer 440 and the through-hole wiring 360a are formed. The second magnetic layer can be formed by the same process as that described above.

[0223] [Sensor parts]

[0224] The inductor component includes the circuit substrate of the present invention. When such an inductor component includes the circuit substrate obtained by the method for manufacturing the circuit substrate of the first embodiment, at least a portion of the surrounding area of ​​the solidified product of the magnetic paste has an inductor pattern formed of a conductor. Such an inductor component can be applied to the component described in Japanese Patent Application Laid-Open No. 2016-197624, for example.

[0225] In addition, in the case of a circuit substrate obtained by the circuit substrate manufacturing method of the second embodiment, the sensor substrate has a magnetic layer and a conductive structure at least a portion of which is buried in the magnetic layer, and includes a sensor element composed of the conductive structure and a portion of the magnetic layer extending in the thickness direction of the magnetic layer and surrounded by the conductive structure. Here, Fig.13 FIG. 1 is a schematic top view of a sensor substrate having a built-in sensor element, as viewed from one side in its thickness direction. Fig.14 To indicate that Fig.13 The schematic diagram of the cut end surface of the sensor substrate cut at the position indicated by the II-II dot-dash line is shown. Fig.15 FIG. 4 is a schematic top view for explaining the structure of the first conductor layer in the sensor substrate.

[0226] like Fig.13 and Fig.14 As shown as an example in FIG. 1 , the circuit board 100 is a stacked wiring board having a plurality of magnetic layers (a first magnetic layer 320 and a second magnetic layer 340) and a plurality of conductor layers (a first conductor layer 420 and a second conductor layer 440), that is, a stacked magnetic layer and a stacked conductor layer. In addition, the inductor substrate 100 includes an inner substrate 200.

[0227] according to Fig.14, the first magnetic layer 320 and the second magnetic layer 340 constitute the magnetic part 300 which can be regarded as a magnetic layer of one body. Therefore, the coil-shaped conductive structure 400 is provided in a manner that at least a part is buried in the magnetic part 300. That is, in the sensor substrate 100 of the present embodiment, the sensor element is composed of the coil-shaped conductive structure 400 and a part of the magnetic part 300, namely, the core part, which extends in the thickness direction of the magnetic part 300 and is surrounded by the coil-shaped conductive structure 400.

[0228] like Fig.15 As shown as an example in FIG. 4 , the first conductor layer 420 includes: a spiral wiring portion for constituting the coil-shaped conductive structure 400, and a rectangular pad 420a electrically connected to the through-hole wiring 220a. In the example shown in the figure, the spiral wiring portion includes: a straight portion, a bent portion bent at a right angle, and a detour portion detour at the pad 420a. In the example shown in the figure, the spiral wiring portion of the first conductor layer 420 has a shape with an overall outline of a substantially rectangular shape, winding in a counterclockwise direction from the center side to the outside thereof.

[0229] Likewise, the second conductor layer 440 is provided on the first magnetic layer 320. The second conductor layer 440 includes a spiral wiring portion for constituting the coil-shaped conductive structure 400. Fig.13 or Fig.14 In the embodiment, the spiral wiring portion includes a straight portion and a bent portion bent at a right angle. Fig.13 or Fig.14 In the figure, the spiral wiring portion of the second conductor layer 440 has a shape with a generally rectangular outline as a whole and is wound in a clockwise direction from the center side toward the outside thereof.

[0230] Such a sensor component can be used as a wiring board for mounting electronic components such as semiconductor chips, or as a (multi-layer) printed wiring board using the wiring board as an inner substrate. In addition, it can be used as a chip sensor component obtained by monolithicizing the wiring board, or as a printed wiring board with the chip sensor component mounted on the surface.

[0231] In addition, various forms of semiconductor devices can be manufactured using the wiring board. The semiconductor device including the wiring board can be suitably used in electrical products (e.g., computers, mobile phones, digital cameras, and televisions) and transportation vehicles (e.g., motorcycles, cars, trains, ships, and airplanes). Example

[0232] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that in the following description, unless otherwise expressly stated, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass", respectively.

[0233] <Measurement of pH of dispersant 1 (glass electrode method)>

[0234] The pH meter used for the measurement ("HM-41X" manufactured by DKK Toa Co., Ltd.) was calibrated at 22°C using a neutral phosphate standard solution (pH 6.86, manufactured by DKK Toa Co., Ltd.), a phthalate standard solution (pH 4.01, manufactured by DKK Toa Co., Ltd.), and a borate standard solution (pH 9.18, manufactured by DKK Toa Co., Ltd.). A 30% by mass ethanol aqueous solution prepared with 99.5% by volume anhydrous ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and pure water was added in small amounts to each dispersant and dissolved to prepare a measurement sample having a dispersant concentration of 0.067 g / mL. The pH of the prepared measurement sample was measured by the glass electrode method using a pH meter calibrated at 22°C according to the above-mentioned points. The measurement was performed three times, and the average value was taken as the pH of the dispersant.

[0235] <Measurement of pH of dispersant 2 (indicator method)>

[0236] Dissolve the acidic dispersant in acetone to prepare a sample with a dispersant concentration of 0.1 g / mL (22°C). Gently dip the pH test paper into the sample and lift it up to dry the excess water. Observe and compare the color of the wetted part of the test paper with the colorimetric card, and take the pH of the closest color as the pH of each sample.

[0237] <Example 1: Preparation of magnetic paste 1>

[0238] 15 parts by mass of epoxy resin ("ZX-1059", a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, manufactured by Nippon Steel Chemicals Co., Ltd.), 5 parts by mass of epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, manufactured by Nippon Steel Chemicals Co., Ltd.), 1.1 parts by mass of acidic dispersant ("C-2093I", acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on glass electrode method, pH=2 based on indicator method), 1 part by mass of curing agent ("2MZA-PW", imidazole epoxy resin curing agent, manufactured by Shikoku Chemicals Co., Ltd.), and 110 parts by mass of magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3 μm, manufactured by Powdertech Co., Ltd.) are mixed to prepare magnetic paste 1.

[0239] <Example 2: Preparation of magnetic paste 2>

[0240] In Example 1, 5 parts by mass of epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, manufactured by Nippon Steel Chemical Materials Co., Ltd.) was replaced by 5 parts by mass of epoxy resin ("EX-201", resorcinol diglycidyl ether, manufactured by Nagase ChemteX Co., Ltd.), and 1.1 parts by mass of acidic dispersant ("C-2093I", acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on glass electrode method, pH=2 based on indicator method) was replaced by 1.1 parts by mass of acidic dispersant ("SC-1015F", multifunctional comb-type functional polymer with polyoxyalkylene chains, manufactured by NOF Corporation, pH=3.3 based on glass electrode method, pH=3 based on indicator method). Except for the above matters, the same operation as in Example 1 was carried out to prepare magnetic paste 2.

[0241] <Example 3: Preparation of magnetic paste 3>

[0242] In Example 1, the acidic dispersant ("C-2093I", acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on the glass electrode method, pH=2 based on the indicator method) was replaced with 1.1 parts by mass of an acidic dispersant ("DA-375", polyether phosphate, manufactured by Kusumoto Chemicals, pH 3 based on the indicator method, which is insoluble in a 30% by mass ethanol aqueous solution and cannot be measured by the glass electrode method). Except for the above matters, the same operation as in Example 1 was performed to prepare a magnetic paste 3.

[0243] <Example 4: Preparation of magnetic paste 4>

[0244] In Example 1, the amount of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 by glass electrode method, pH=2 by indicator method) was changed from 1.1 parts by mass to 2.2 parts by mass. Except for the above matters, the same operation as in Example 1 was performed to prepare a magnetic paste 4.

[0245] <Example 5: Preparation of magnetic paste 5>

[0246] In Example 1,

[0247] 1) The amount of epoxy resin ("ZX-1059", a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, manufactured by Nippon Steel Chemicals Co., Ltd.) was changed from 15 parts by mass to 18 parts by mass,

[0248] 2) 5 parts by mass of epoxy resin ("ZX-1658GS", cyclic aliphatic diglycidyl ether, manufactured by Nippon Steel Chemicals Co., Ltd.) was replaced with 2 parts by mass of epoxy resin ("EX-201", resorcinol diglycidyl ether, manufactured by Nagase ChemteX Co., Ltd.),

[0249] 3) The amount of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH = 2.9 by glass electrode method, pH = 2 by indicator method) was changed from 1.1 parts by mass to 0.8 parts by mass,

[0250] 4) The amount of magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3 μm, manufactured by Powdertech Co., Ltd.) was changed from 110 parts by mass to 75 parts by mass;

[0251] Except for the above matters, the same operation as in Example 1 was carried out to prepare a magnetic paste 5.

[0252] <Example 6: Preparation of magnetic paste 6>

[0253] In Example 1,

[0254] 1) The amount of epoxy resin ("ZX-1059", a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, manufactured by Nippon Steel Chemicals Co., Ltd.) was changed from 15 parts by mass to 5 parts by mass,

[0255] 2) The amount of epoxy resin ("ZX1658GS", cyclic aliphatic diglycidyl ether, manufactured by Nippon Steel Chemicals Co., Ltd.) was changed from 5 parts by mass to 10 parts by mass,

[0256] 3) The amount of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH = 2.9 by glass electrode method, pH = 2 by indicator method) was changed from 1.1 parts by mass to 2.5 parts by mass,

[0257] 4) The amount of magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3 μm, manufactured by Powdertech Co., Ltd.) was changed from 110 parts by mass to 250 parts by mass;

[0258] Except for the above matters, the same operation as in Example 1 was carried out to prepare a magnetic paste 6.

[0259] <Example 7: Preparation of magnetic paste 7>

[0260] In Example 4, the amount of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on the glass electrode method, pH=2 based on the indicator method) was changed from 2.2 parts by mass to 3 parts by mass, and 110 parts by mass of the magnetic powder ("M05S", Fe-Mn ferrite, average particle size 3 μm, manufactured by Powdertech Co., Ltd.) was changed to 150 parts by mass of the magnetic powder ("AW2-08 PF3F", Fe-Cr-Si alloy (amorphous), average particle size 3.0 μm, manufactured by EPSON ATMIX Co., Ltd.). Except for the above matters, the same operation as in Example 4 was carried out to prepare a magnetic paste 7.

[0261] <Comparative Example 1: Preparation of Magnetic Paste 8>

[0262] In Example 1, 1.1 parts by mass of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH 2.9 by glass electrode method, pH 2 by indicator method) was replaced with 1.1 parts by mass of the dispersant ("SN-WET 125", a silicone surfactant, manufactured by Sannopco, pH = 7.5 by glass electrode method, pH = 7 by indicator method). Except for the above matters, the same operation as in Example 1 was performed to prepare a magnetic paste 8.

[0263] <Comparative Example 2: Preparation of Magnetic Paste 9>

[0264] In Example 1, 1.1 parts by mass of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on the glass electrode method, pH=2 based on the indicator method) was replaced with 1.1 parts by mass of the dispersant ("SN-WET 980", a silicone surfactant, manufactured by San Nopco, pH=9.8 based on the glass electrode method, pH=9 based on the indicator method). Except for the above matters, the same operation as in Example 1 was performed to prepare a magnetic paste 9.

[0265] <Comparative Example 3: Preparation of Magnetic Paste 10>

[0266] In Example 1, 1.1 parts by mass of the acidic dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 based on the glass electrode method, pH=2 based on the indicator method) was replaced with 1.1 parts by mass of the dispersant ("DOPA-100", a dispersant for silica, manufactured by Kyoeisha Chemical Co., Ltd., pH=9.9 based on the glass electrode method, pH=11 based on the indicator method). Except for the above matters, the same operation as in Example 1 was performed to prepare a magnetic paste 10.

[0267] <Comparative Example 4: Preparation of Magnetic Paste 11>

[0268] In Example 1, 1.1 parts by mass of a dispersant ("C-2093I", an acidic dispersant for nanoparticles, manufactured by NOF Corporation, pH=2.9 by glass electrode method, pH=2 by indicator method) was not used. Magnetic paste 11 was prepared in the same manner as in Example 1 except for the above matters.

[0269] <Measurement of Viscosity of Magnetic Paste>

[0270] The temperature of magnetic pastes 1 to 11 was maintained at 25±2°C, and the viscosity at 25°C was measured using an E-type viscometer ("RE-80U" manufactured by Toki Sangyo Co., Ltd., 3°×R9.7 cone (conical rotor), rotation speed of 5 rpm). In addition, the measured viscosity was evaluated according to the following criteria from the viewpoints of printability and ease of bubble release;

[0271] ○: Less than 100 Pa・s

[0272] △: 100 Pa・s or more and less than 200 Pa・s

[0273] ×: 200 Pa・s or more.

[0274] <Measurement of Viscosity of Magnetic Paste After 1 Week>

[0275] The magnetic pastes 1 to 11 were left for 1 week while being kept at 25±2°C. The viscosity at 25°C was measured using an E-type viscometer ("RE-80U" manufactured by Toki Sangyo Co., Ltd., 3°×R9.7 cone (conical rotor), rotation speed of 5 rpm). In addition, the measured viscosity was evaluated according to the following criteria from the viewpoints of printability and ease of bubble release;

[0276] ○: Less than 100 Pa・s

[0277] △: 100 Pa・s or more and less than 200 Pa・s

[0278] ×: 200 Pa・s or more.

[0279] <Measurement of mechanical strength (tensile breaking strength)>

[0280] As a support, a polyethylene terephthalate (PET) film treated with a silicone release agent ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) was prepared. Each magnetic paste 1 to 11 was evenly applied on the release surface of the above-mentioned PET film using a scraper so that the thickness of the paste layer after drying became 100 μm, thereby obtaining a magnetic sheet. The obtained magnetic sheet was heated at 180°C for 90 minutes to thermally cure the paste layer, and the support was peeled off to obtain a sheet-like cured product. The tensile breaking strength of the obtained sample was measured in accordance with JIS K7127. The measurement results were evaluated according to the following criteria;

[0281] ○: 50 MPa or more

[0282] △: 40 MPa or more and less than 50 MPa

[0283] ×: less than 40 MPa.

[0284] <Measurement of adhesion strength with copper plating>

[0285] As the inner layer substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.3 mm, R5715ES manufactured by Panasonic Electric Works Co., Ltd.) was prepared by etching both sides by 1 μm with a microetchant (CZ8100 manufactured by MEC Corporation) to roughen the copper surface.

[0286] Each magnetic paste 1 to 11 was uniformly applied to the inner substrate using a scraper so that the thickness of the paste layer after drying was 50 μm to form a paste layer. The paste layer was heated at 130° C. for 30 minutes and then at 145° C. for 30 minutes to thermally cure and form a magnetic layer. The surface of the formed magnetic layer was polished and then heated at 180° C. for 30 minutes for heat treatment.

[0287] The inner substrate with the surface of the magnetic layer polished was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. After annealing at 150°C for 30 minutes, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 30 μm on the magnetic layer. Then, annealing was performed at 180°C for 60 minutes. This substrate was used as an evaluation substrate.

[0288] A cut of 10 mm in width and 100 mm in length was formed on the conductor layer of the evaluation substrate, one end of the cut was peeled off and clamped with a clamp (manufactured by TSE Co., Ltd., AUTO COM type tester "AC-50C-SL"), and the load (kgf / cm) when 35 mm was peeled off in the vertical direction at a speed of 50 mm / min at room temperature was measured. The obtained results were evaluated according to the following criteria;

[0289] ○: 0.2 kgf / cm or more

[0290] ×: Less than 0.2 kgf / cm.

[0291] <Measurement of relative magnetic permeability and magnetic loss>

[0292] As a support, a polyethylene terephthalate (PET) film treated with a silicone release agent ("PET501010" manufactured by Lintec Co., Ltd., thickness 50 μm) was prepared. Each magnetic paste 1 to 11 was evenly applied to the release surface of the above-mentioned PET film with a scraper under the condition that the thickness of the paste layer after drying became 100 μm, thereby obtaining a magnetic sheet. The paste layer was thermally cured by heating the obtained magnetic sheet at 180°C for 90 minutes, and the support was peeled off to obtain a sheet-like cured product. The obtained cured product was cut into test pieces with a width of 5 mm and a length of 18 mm as evaluation samples. For this evaluation sample, the relative magnetic permeability (μ') and magnetic loss (μ'') were measured by a three-turn coil method at a measurement frequency of 100 MHz and a room temperature of 23°C using "HP8362B" manufactured by Agilent Technologies.

[0293] [Table 1]

[0294] .

[0295] <Manufacturing of circuit boards>

[0296] As an inner layer substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.3 mm, “R5715ES” manufactured by Panasonic Electric Works Co., Ltd.) was prepared.

[0297] After forming through holes with a diameter of 0.35 mm at a pitch of 1 mm on the inner layer substrate, a roughening process was performed. As a roughening process, the through holes were immersed in Swelling Dip Securiganth P containing diethylene glycol monobutyl ether manufactured by Atotech Japan Co., Ltd. as a swelling liquid at 60°C for 5 minutes, and then immersed in Concentrate Compact P (KMnO4: 60g / L, NaOH: 40g / L aqueous solution) manufactured by Atotech Japan Co., Ltd. as a roughening liquid at 80°C for 10 minutes, and finally immersed in Reduction solution Securiganth P manufactured by Atotech Japan Co., Ltd. as a neutralizing liquid at 40°C for 5 minutes after washing. Then, it was dried at 130°C for 15 minutes. Thus, the through hole wall surface was roughened and decontaminated.

[0298] Next, after being immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, it was immersed in an electroless copper plating solution at 25°C for 20 minutes. After being annealed at 150°C for 30 minutes, copper sulfate electrolytic plating was performed. Then, annealing was performed at 190°C for 60 minutes to form a plating layer in the through hole, thereby obtaining a through-hole substrate.

[0299] The magnetic paste 1 prepared in Example 1 was printed on the through-hole substrate to fill the through-holes with the magnetic paste 1 to form a paste layer. After the paste layer was formed, it was heated at 130° C. for 30 minutes and further heated at 150° C. for 30 minutes.

[0300] Next, the surfaces of the paste layer and the through-hole substrate were buffed and polished, and then heated at 180° C. for 30 minutes to thermally cure the paste layer, thereby obtaining a magnetic layer.

[0301] The through-hole substrate was immersed in an electroless plating solution containing PdCl2 at 40°C for 5 minutes, and then immersed in an electroless copper plating solution at 25°C for 20 minutes. After heating at 150°C for 30 minutes for annealing, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 30 μm on the magnetic layer. Then, annealing was performed at 180°C for 60 minutes. Then, an anti-corrosion layer was formed, and patterning was performed by etching to obtain a circuit substrate.

[0302] In this circuit board, there was no peeling or swelling at the interface between the surface of the magnetic layer and the conductor layer, and the plating adhesion was good.

[0303] Explanation of symbols

[0304] 10-core substrate

[0305] 11 Support base plate

[0306] 12. First Metal Layer

[0307] 13. Second Metal Layer

[0308] 14 Through Holes

[0309] 20 Plating

[0310] 30a Magnetic paste

[0311] 30 Magnetic layer

[0312] 40 Conductor layer

[0313] 41 pattern conductor layer

[0314] 100 Circuit board

[0315] 200 Inner substrate

[0316] 200a First main surface

[0317] 200b Second main surface

[0318] 220 Through hole

[0319] 220a Through-hole wiring

[0320] 240 external terminals

[0321] 300 Magnetics

[0322] 310 Magnetic Sheet

[0323] 320a Resin composition layer

[0324] 320 First insulation layer

[0325] 330 Support

[0326] 340 Second insulation layer

[0327] 360 holes

[0328] 360a through-hole wiring

[0329] 400 Coil-shaped conductive structure

[0330] 420 First conductor layer

[0331] 420a pad

[0332] 440 second conductor layer.

Claims

1. A magnetic paste comprising: (A) Magnetic powder, (B) Epoxy resin, (C) an acidic dispersant, and (D) a curing agent, The viscosity of the magnetic paste at 25°C is 200 Pa·s or less. The content of the organic solvent is less than 1.0 mass % relative to the total mass of the magnetic paste, or the organic solvent is not contained.

2. The magnetic paste according to claim 1, wherein The pH of the component (C) is lower than 4.

3. The magnetic paste according to claim 1, wherein The pH of the component (C) is 3.3 or less.

4. The magnetic paste according to claim 1, wherein The pH of the component (C) is 2 or more.

5. The magnetic paste according to claim 1, wherein The pH of the component (C) is 2.4 or more.

6. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (C) is 0.1 mass % or more and 5 mass % or less.

7. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (C) is 0.5 mass % or more.

8. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (C) is 3 mass % or less.

9. The magnetic paste according to claim 1, wherein The component (D) contains an imidazole-based epoxy resin curing agent.

10. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (D) is 0.1 mass % or more.

11. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (D) is 0.5 mass % or more.

12. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (D) is 5 mass % or less.

13. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (D) is 1 mass % or less.

14. The magnetic paste according to claim 1, wherein The component (A) is at least one selected from the group consisting of iron oxide powder and iron alloy metal powder.

15. The magnetic paste according to claim 1, wherein (A) component comprises iron oxide powder, The iron oxide powder includes ferrite containing at least one element selected from the group consisting of Ni, Cu, Mn and Zn.

16. The magnetic paste according to claim 1, wherein The component (A) includes an iron alloy metal powder containing at least one element selected from the group consisting of Si, Cr, Al, Ni and Co.

17. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (A) is 70 mass % or more and 98 mass % or less.

18. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (A) is 80 mass % or more.

19. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (A) is 90 mass % or less.

20. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (B) is 1 mass % or more.

21. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (B) is 10 mass % or more.

22. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (B) is 35 mass % or less.

23. The magnetic paste according to claim 1, wherein When the nonvolatile matter in the magnetic paste is 100 mass %, the content of the component (B) is 20 mass % or less.

24. The magnetic paste according to claim 1, wherein The component (B) contains a liquid epoxy resin.

25. The magnetic paste according to claim 1, wherein The component (C) contains a liquid acidic dispersant.

26. The magnetic paste according to claim 1, which is used to fill a through hole. 27 . A cured product, which is a cured product of the magnetic paste according to claim 1 .

28. A circuit substrate comprising: A substrate having a through hole, and A cured product of the magnetic paste according to any one of claims 1 to 26 filled in the through-hole.

29. An inductor component comprising the circuit substrate according to claim 28.